2020
DOI: 10.1155/2020/9539674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Vitamin B1 and Mecobalamin on Dry Eye Disease

Abstract: Purpose. To assess the effects of oral vitamin B1 and mecobalamin on dry eye disease (DED) and patient satisfaction with treatment. Methods. In this randomized controlled study, DED patients were divided into 4 groups based on treatment: group 1, only artificial tears; group 2, corticosteroid eye drops and artificial tears; group 3, oral vitamin B1, mecobalamin, and artificial tears; and group 4, oral vitamin B1, mecobalamin, corticosteroid eye drops, and artificial tears. DED symptoms, signs, and patient sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The three objective outcome parameters of DED the study examined all showed significantly greater improvement in the vitamin D supplemented group. This supports the large number of observational studies which have suggested a link between vitamin D deficiency and DED [173]. Oral vitamin B12 and thiamine were administered as a combined supplement in an RCT by Ren et al [174] in a total patient cohort of 152 eyes, finding significant improvements in both subjective and objective outcome measures.…”
Section: The Gut-eye Axis and The Treatment Of Dedsupporting
confidence: 58%
“…The three objective outcome parameters of DED the study examined all showed significantly greater improvement in the vitamin D supplemented group. This supports the large number of observational studies which have suggested a link between vitamin D deficiency and DED [173]. Oral vitamin B12 and thiamine were administered as a combined supplement in an RCT by Ren et al [174] in a total patient cohort of 152 eyes, finding significant improvements in both subjective and objective outcome measures.…”
Section: The Gut-eye Axis and The Treatment Of Dedsupporting
confidence: 58%
“…It has been reported that the combination of vitamin C and vitamin E attenuates the neuropathic pain behavior by synergistic antinociceptive effects, although vitamin C or vitamin E given alone failed to reduce the nociceptive behavior ( 39 ). Thiamine, which reduces peripheral neuropathic pain ( 41 ), attenuates symptoms of dry eye ( 15 ). Riboflavin supplementation reduces hyperalgesia and inflammation ( 42 ) and inhibits histamine-dependent itch by modulating transient receptor potential vanilloid 1 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tocopherol, ascorbic acid, and β-carotene are antioxidants that reduce oxidative stress and inflammation of the ocular surface ( 14 ). Thiamine nitrate ( 15 ) and pyridoxine ( 14 ) have been reported to ameliorate dry eye. Oral multivitamin drug (MVG; Greenwol soft cap, Kyungnam Pharm.)…”
Section: Introductionmentioning
confidence: 99%
“…53 Finally, cobalamin has been linked to dry eye disease and has been used as a treatment for pain associated with dry eye disease. 65,66 A study by Ozen et al, found that treating vitamin B12 deficiency in patients with dry eye disease in addition to topical treatment improved the neuropathic pain. 66 Another case report in 2015 of a 28-year-old patient with bilateral burning pain and foreign body sensation in both eyes was found to have cobalamin deficiency.…”
Section: Ocular Manifestationsmentioning
confidence: 99%